Electron Microscope Scanning, and Antibacterial Activity of Tio2 Nanoparticles on pathogenic strains of Staphylococcus aureus and Escherichia coli - Manar Abd Alrazaq Hassan ,; N.A. Hassan ,; Shahad Khudhair Khalaf ,; Ali hakiem tawfieq (Diyala Journal of Medicine, 2024)
Background: Nanoparticles are increasingly being used as an alternative antibiotic to target microorganisms, particularly for treating bacterial infections. In current study it was recognized processes such as metal ion release, induction of oxidative stress, and non-oxidative mechanisms. Developing resistance to nanoparticles is challenging for bacterial cells due to the multiple simultaneous actions against microorganisms, and require several simultaneous gene alterations within the same bacterial cell.